Differential colorectal carcinogenesis:Molecular basis and clinical relevance - Morán, Alberto; Ortega, Paloma; de Juan, Carmen; Fernández-Marcelo, Tamara; Frías, Cristina; Sánchez-Pernaute, Andrés; Torres, Antonio José; Díaz-Rubio, Eduardo; Iniesta, Pilar; Benito, Manuel (World journal of gastrointestinal oncology, 2010)
Colorectal cancer(CCR) is one of the most frequent cancers in developed countries.It poses a major public health problem and there is renewed interest in understanding the basic principles of the molecular biology of colorectal cancer.It has been established that sporadic CCRs can arise from at least two different carcinogenic pathways.The traditional pathway,also called the suppressor or chromosomal instability pathway,follows the Fearon and Vogelstein model and shows mutation in classical oncogenes and tumour suppressor genes,such as K-ras,adenomatous polyposis coli,deleted in colorectal cancer,or p53.Alterations in the Wnt pathway are also very common in this type of tumour.The second main colorectal carcinogenesis pathway is the mutator pathway.This pathway is present in nearly 15% of all cases of sporadic colorectal cancer.It is characterized by the presence of mutations in the microsatellite sequences caused by a defect in the DNA mismatch repair genes,mostly in hMLH1 or hMSH2.These two pathways have clear molecular differences,which will be reviewed in this article,but they also present distinct histopathological features.More strikingly,their clinical behaviours are completely different,having the "mutator" tumours a better outcome than the "suppressor" tumours.